Training evaluation - Kukarni, P.K. (2008)
Training programmes need time, money and energy. Therefore, an organization should assess investment in training through evaluation. Evaluation helps to take specific action for improvement. An organization is more concerned with evaluating the specific results of training as measured by changes in the performance of the workers on the job. But still, there is no scientific formula to evaluate management training. There is a need to develop a satisfactory scientific formula to evaluate effectiveness of management training. Because training not only develops on individual but also leads to organization development. - Reproduced.
Keywords: Training